Redefining the Practice of the Old Profession with Technology: Sex Work and the Use of Whatsapp for Clientele Management: WhatsApp for Clentelle Management by Sex Workers - Sekyi, Naa Adjeley Suta Alakija; Bervell, Brandford; Arkorful, Valentina (Advances in Social Sciences Research Journal, 2021)
Technology has revolutionized the culture within contemporary society. Especially for communication and sharing of information, social media has taken the epicenter. The proliferation of social media technologies in our daily communication has infiltrated into all facets of life from education, commerce, family and friends, relations etc. However, an aspect of socio-cultural life which is sex trade has also been influenced by social media technological diffusion. A notable and popular social media platform today purported to be complementing the activities of sex workers is the WhatsApp technology. In view of this, the study focuses on unraveling the actual use of WhatsApp by sex workers in managing their clients. Accordingly, the study employed the qualitative approach with the phenomenological transcendental design to find out actual usage experiences of commercial sex workers in the Cape Coast metropolis of Ghana. A purposive sample based on snowballing technique was used to collect data from fifteen (15) sex workers based on a semi-structured interview guide. A thematic analysis centred on a deductive approach was used to analyze the qualitative data. The findings revealed that sex workers had favourable and positive impressions or attitude towards WhatsApp usage. They also found WhatsApp to be very useful and benefitted immensely from it in various ways. Irrespective of this, sex workers were beset with challenges such as stigma from future leakage of their nude information as well as internet network constraints in using WhatsApp. The study derived a model based on the findings for future validation through quantitative modelling analysis.